PENEGAKAN HUKUM TERHADAP PRAKTIK JUAL BELI DARAH BERDASARKAN UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN DI KOTA PEKANBARU - Muhammad Rizky; Mexsasai Indra; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The use of blood as one of the drugs that has not been replaced in recent times has increased, whilethe source of blood is still from humans themselves, giving rise to a imbalance between the provision ofblood and blood needs which can cause, the emergence of buying and selling blood that is not inaccordance with the nation's philosophy. There is a practice of buying and selling blood at the hospitalwhich in addition to breaking the rules and there is no guarantee that the blood transfused to patients ishygienic and sterile.In this thesis writing, the research used is juridical psychological research, namely researchconducted by making legal identification and how the effectiveness of the implementation of the law appliesin the community. Because in this study the author immediately conducted research on the location or placeunder study to provide a complete and clear picture of the problem under study. In this study the authorsdetermined the study population related to the object of research by the authors at the Indonesian Red Crossin Pekanbaru City. As for the population in this study were the Head of the Indonesian Red Cross ofPekanbaru City, the Doctor of the Indonesian Red Cross in Pekanbaru City, the victim of the practice ofbuying and selling blood in the city of Pekanbaru.From the results of the study the authors concluded that law enforcement on the practice of buyingand selling blood based on Law Number 36 of 2009 concerning Health in Pekanbaru City can be enforcedproperly, but in the implementation of law enforcement by the police and other law enforcement officersoften experience it is this obstacle through law enforcement that the law becomes a reality. Inhibitingfactors in law enforcement against the practice of buying and selling blood based on Law Number 36 of2009 concerning Health in Pekanbaru City faced in law enforcement of criminal acts of reclamation, thereare 2 factors, namely internal and external factors.Keywords: Law Enforcement - Practices To Sell Blood.